ANALISIS FAKTOR EKSTERNAL DAN INTERNAL SEBAGAI DASAR PERUMUSAN STRATEGI BISNIS UD SEKAR JATI STAR JOMBANG - DIAN OKTAVIA SARI, IKE (Jurnal Akuntansi AKUNESA, 2018)
Globalization makes the competition in the business world is increasing. One of the small and medium enterprises who feel the competition is UD Sekar Jati Star. Over the past six years, UD Sekar Jati Star fluctuations in sales as a result of the increasing number of competitors. Fluctuations in sales numbers indicate that management Sekar Jati UD Star does not implement the concept of management strategy well. This study aims to determine a suitable business strategy applied by UD Sekar Jati Star based on internal and external factors in order to cope with fluctuations in sales. This research approach using a mixed method approach. Subjects in this study is the owner of the company and the employees of UD Sekar Jati Star. The collection of data used in this study were interviews, questionnaires, observation, and documentation. The results of this study indicate that based on a matrix IE, the company is in the first quadrant, which means the company is in a position to grow and build so that a suitable strategy for the company is intensive strategy (market penetration, market development, and product development) and integrative strategy (forward integration, backward integration, and horizintal integration). Based on QSPM matrix, the most appropriate strategy to be applied by UD Sekar Jati Star is a product development. Keywords: strategy formulation, SWOT analysis, QSPM